Adoption Experiences and the Tracing and Narration of Family Genealogies - Kirton, Derek (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This edited collection explores the linkages between adoption and genealogy. With its inevitable genealogical disruptions, adoption offers many interesting avenues to explore a range of psychosocial phenomena. Through both conventional research and means such as creative writing, literary criticism, and media analysis, contributors offer wide ranging perspectives on the key questions of genealogy in adoption. They do this in varied ways, reflecting different theoretical approaches and focal points on those impacted by adoption. Core issues include those of kinship, identity, and belonging. Within adoption, these link not only to personal and interpersonal experiences and relationships, but also to intersections with the workings of class, gender, sexuality, ethnicity, and nation (the latter two are often captured in debates regarding transracial and international adoption). Many important sites and modes of practice are highlighted, such as adoption searches and reunions, openness, access to records, and the community activism that is related to these activities. Although these have long histories, they have also been evolving with the growing importance of social media, online genealogical tools, and DNA testing. Reproductive technologies have similarly evolved, and questions relating to genealogy in adoption are mirrored in relation to donor-assisted conceptions. All these important and intriguing issues are addressed in this volume.